Isopluvial Analysis and Intensity Duration Frequency (IDF) Curves for different cities in India - Das, AshokKumar; SRIVASTAVA , PRAGATI; YADAV, BP (MAUSAM, 2022)
Globally water resource management is becoming a priority for every Government. This is due to tremendous increase in population growth,urbanization, modern life style, increase in agricultural activities, industrialization etc. which is increasing the water demand day by day. This paper focuses on design storms studiesusing return period analysis technique (Isopluvial analysis) based on 129 well distributedSelf Recording Raingauge (SRRG) stations in the various climatic zones of India. The extreme rainfall values are taken for preparation of Isopluvial maps for return period of 2-year, 5- year, 10-year, 25-year, 50-year and 100-year at1-hour, 3-hour, 6-hour, 12-hour and 24-hour duration. Further, station wise Intensity Duration Frequency (IDF) curves are also prepared for 27 stations of the country. The Gumble distribution technique for extreme rainfall series is used for this study. Isopluvial maps & IDF curves are found very useful for Design engineers, hydrologists and hydraulic-consultants for the purpose of planning & designing of water resources related projects in the country forthe construction of any drainage network system, metro, road ways etc.and also, to some extend for the estimation of availability of water.